Efficacy and safety of a digital check-in and triage kiosk in emergency departments: a systematic review protocol - Benedict Hayhoe; Azeem Majeed; Mark Harmon; Geva Greenfield; Ana Luísa Neves; Himani Laxshmi Kaur Sehgal (BMJ Open)
Introduction Increasing demand for healthcare services worldwide has led to unprecedented challenges in managing patient flow and delivering timely care in emergency care settings. Overcrowding, prolonged waiting times, reduced patient satisfaction and increased mortality are some of the consequences of this increased demand. To address this issue, some healthcare providers have turned to digital systems, such as self-check-in kiosks, for efficient patient triage and prioritisation. While digital triage systems hold promise for efficient patient prioritisation, reduced data duplication, shorter waiting times, improved patient satisfaction, the impact on workflow, the accuracy of triage and staff workload require further exploration for successful implementation in emergency care settings. This systematic review aims to assess the efficacy and safety of digital check-in and triage kiosk implementation within emergency departments.Methods and analysis A systematic review will be conducted in MEDLINE (Ovid), Web of Science, Scopus and Science Direct and will include quantitative and mixed method studies with a significant quantitative component, related to self-service kiosk implementation in emergency departments. The outcomes of interest will focus on the efficacy and safety of digital triage, including triage time, workflow, the diagnostic accuracy of triage and adverse events. Risk of bias will be assessed using the Cochrane Risk of Bias Tool. A narrative synthesis will be used to summarise the findings of the included studies.Ethics and dissemination This review is exempt from ethical approval because it will be analysing published studies containing non-identifiable data. The findings will be disseminated through peer-reviewed publications.PROSPERO registration number CRD42024481506.